A facilely synthesized polyanionic gel adsorbent with high adaptability and new adsorption effects for purification of Cu(II)‐containing wastewater. Issue 11 (30th August 2019) - Li, Hongyan; Song, Chunli; Bai, Yu; Yu, Yikai
Abstract: BACKGROUND: Cu(II)‐containing wastewater causes serious pollution of the water environment. Adsorption is one of the most commonly used water purification methods, with the selection of suitable adsorbents being the key factor. This motivates the development of new efficient adsorbents to purify Cu(II)‐containing wastewater. RESULTS: A highly adaptable polyanionic gel (PAG) was synthesized by the facile crosslinking copolymerization of acrylic acid (AA) and triallylmethylammonium chloride (TAMAC) at 65 °C for 0.5 h, followed by a simple neutralization treatment, avoiding the inconvenience of the complex and expensive preparation process required to prepare existing adsorbents. When first used as an adsorbent material, PAG achieved highly efficient purification of a wide concentration range of 10–2000 mg L −1 Cu(II)‐containing wastewater. The PAG adsorption capacity for Cu(II) was 222.2 mg g −1, which was higher than the values of selected existing adsorbent materials (9.50–214 mg g −1 ), and PAG had the advantages of being eco‐friendly, facilely obtained and regenerable. Also, PAG maintained stable adsorption ability even when the adsorption temperature varied from 30 to 50 °C. Moreover, a series of new adsorption effects were first observed as the key factors for PAG adsorption to achieve high adaptability. CONCLUSION: Generally, considering the comprehensive performances, PAG would have higher adaptability in the efficient purification of different concentrations and different temperatures of Cu(II)‐containing wastewater. It would thus have better application in different water environments and be regarded as a better adsorbent alternative. © 2019 Society of Chemical Industry